Microbes influence the biogeochemical and optical properties of maritime Antarctic snow - Hodson, Andrew; Nowak, Aga; Cook, Joseph; Sabacka, Marie; Wharfe, Emma S; Pearce, David Anthony; Convey, Peter; Vieira, Gonçalo (Journal of Geophysical Research: Biogeosciences, 2017)
Snowmelt in the Antarctic Peninsula region has increased significantly in recent decades, leading to greater liquid water availability across a more expansive area. As a consequence, changes in the biological activity within wet Antarctic snow require consideration if we are to better understand terrestrial carbon cycling on Earth's coldest continent. This paper therefore examines the relationship between microbial communities and the chemical and physical environment of wet snow habitats on Livingston Island of the maritime Antarctic. In so doing, we reveal a strong reduction in bacterial diversity and autotrophic biomass within a short (<1 km) distance from the coast. Coastal snowpacks, fertilized by greater amounts of nutrients from rock debris and marine fauna, develop obvious, pigmented snow algal communities that control the absorption of visible light to a far greater extent than with the inland glacial snowpacks. Absorption by carotenoid pigments is most influential at the surface, while chlorophyll is most influential beneath it. The coastal snowpacks also indicate higher concentrations of dissolved inorganic carbon and CO2 in interstitial air, as well as a close relationship between chlorophyll and dissolved organic carbon (DOC). As a consequence, the DOC resource available in coastal snow can support a more diverse bacterial community that includes microorganisms from a range of nearby terrestrial and marine habitats. Therefore, since further expansion of the melt zone will influence glacial snowpacks more than coastal ones, care must be taken when considering the types of communities that may be expected to evolve there.
Keywords: Antarktis; biogeokjemi; mikrobiologi; mikroorganismer; snøalger; snøpakke; snøsmelting

Some like it cold: microbial transformations of mercury in polar regions - Barkay, Tamar; Kroer, Niels; Poulain, Alexandre J (Polar Research, 2011)
The contamination of polar regions with mercury that is transported from lower latitudes as inorganic mercury has resulted in the accumulation of methylmercury (MeHg) in food chains, risking the health of humans and wildlife. While production of MeHg has been documented in polar marine and terrestrial environments, little is known about the responsible transformations and transport pathways and the processes that control them. We posit that as in temperate environments, microbial transformations play a key role in mercury geochemical cycling in polar regions by: (1) methylating mercury by one of four proposed pathways, some not previously described; (2) degrading MeHg by activities of mercury resistant and other bacteria; and (3) carrying out redox transformations that control the supply of the mercuric ion, the substrate of methylation reactions. Recent analyses have identified a high potential for mercury-resistant microbes that express the enzyme mercuric reductase to affect the production of gaseous elemental mercury when and where daylight is limited. The integration of microbially mediated processes in the paradigms that describe mercury geochemical cycling is therefore of high priority especially in light of concerns regarding the effect of global warming and permafrost thawing on input of MeHg to polar regions. Keywords: Microbiology; mercury biogeochemistry; redox transformations; polar regions; methylation
Keywords: Antarktis; biogeokjemi; forurensning; mikrobiologi; miljøvern; polarområdene; økosystemer

Meteoritten som vitnet om liv på Mars - Knutsen, Henning; Matland, Aleksander (Naturen, 2011)
Har livet på Jorda blitt ført hit fra tidligere liv på planeten Mars? I 1996 hevdet en gruppe forskere at en meteoritt fra Mars faktisk inneholdt spor etter organisk liv. Hvis dette virkelig var tilfelle, ville det medføre en revolusjon for vårt syn på verden og det univers vi befinner oss i. Men vitenskapsfolk besitter sunn skepsis, og hos dem kommer ikke tvilen tiltalte til gode. Nå mener de fleste ekspertene at funnet var for godt til å være sant.
Keywords: Antarktis; astrofysikk; mikrobiologi

Using fluorescence to characterize dissolved organic matter in Antarctic sea ice brines - Stedmon, Colin A; Thomas, David N; Papadimitriou, Stathys; Granskog, Mats A; Dieckmann, Gerhard S (Journal of Geophysical Research: Biogeosciences, 2011)
Sea ice plays a dynamic role in the air-sea exchange of CO2. In addition to abiotic inorganic carbon fluxes, an active microbial community produces and remineralizes organic carbon, which can accumulate in sea ice brines as dissolved organic matter (DOM). In this study, the characteristics of DOM fluorescence in Antarctic sea ice brines from the western Weddell Sea were investigated. Two humic-like components were identified, which were identical to those previously found to accumulate in the deep ocean and represent refractory material. Three amino-acid-like signals were found, one of which was unique to the brines and another that was spectrally very similar to tryptophan and found both in seawater and in brine samples. The tryptophan-like fluorescence in the brines exhibited intensities higher than could be explained by conservative behavior during the freezing of seawater. Its fluorescence was correlated with the accumulation of nitrogen-rich DOM to concentrations up to 900 μmol L−1 as dissolved organic carbon (DOC) and, thus, potentially represented proteins released by ice organisms. A second, nitrogen-poor DOM fraction also accumulated in the brines to concentrations up to 200 μmol L−1 but was not correlated with any of the fluorescence signals identified. Because of the high C:N ratio and lack of fluorescence, this material is thought to represent extracellular polymeric substances, which consist primarily of polysaccharides. The clear grouping of the DOM pool into either proteinaceous or carbohydrate-dominated material indicates that the production and accumulation of these two subpools of DOM in sea ice brines is, to some extent, decoupled.
Keywords: Sørishavet; Weddellhavet; fluorescens; gassutveksling; havis; karbondioksid; marin økologi; mikrobielle organismer; mikrobiologi; sjøis